"Raw juicing" – an online study of the home manufacture of anabolic androgenic steroids (AAS) for injection in contemporary performance and image enhancement (PIED) culture. Issue 1 (March 2018) - Brennan, Rebekah; Wells, John S.G.; Van Hout, Marie Claire
Abstract: Background: New evidence with regard to an under documented practice – the home manufacture of anabolic androgenic steroids (AAS) for injection, known as 'homebrewing' – in contemporary injecting performance and image enhancing drug (PIED) culture is the subject of this paper. Methods: Data was collected from five publicly accessible internet discussion forums and coded using NVivo software. For the purposes of this study, threads in relation to homebrewing (n = 14) were extracted from the final set of records for ethnographic content analysis. Results: Motivation to perform homebrewing was largely grounded in the circumnavigation of unreliable online sourcing routes for AAS products, financial losses and potential harms associated with contaminated and counterfeit injectables. Instructions on how to perform homebrewing were found within discussion threads. Identified areas of concern included potential for sterility and dosing issues, injecting harms, isolation from health services. Conclusion: This study provides a snapshot of online communal activity around practice of homebrewing AAS amongst individuals who inject AAS. Further research in this area is warranted, and will be of benefit to healthcare workers, treatment providers and policy makers particularly as this relates to evidence informed and targeted harm reduction policies and effective public health interventions.